Bimbingan Teknis Terhadap Penambang Sumur Minyak Ilegal di Dusun Keban I Kecamatan Sanga Desa Kabupaten Musi Banyuasin Sumatera Selatan - Taufik Arief; Nukman Nukman; Eddy Ibrahim; Nina Tanzerina; Alieftiyani Paramita Gobel (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Oil mining business has been started since the Dutch era, especially in Musi Banyuasin Regency in Keban Village, Sangadesa District. Over time, oil mining operations began to decrease because reserves were no longer economical (cut off), leaving old wells behind. Old wells are scattered sporadically in 12 Districts with a total of ± 1,500 old wells (Petromuba Data, 2021). Several locations are managed by Petromuba Regional Companies (BUMD) and Medco as well as Conoco Philip in Sungai Lilin and Bayung Lincir. Illegal well mining activities (illegal drilling) are carried out in the traditional way, both crude oil drilling equipment, drilling results storage, processing (refinery) and well closure (cut off). Mining of oil wells is illegal, there have been several work accidents in the form of blow outs in 2015, 2017, 2021 and 2022 resulting in 11 deaths. Given the ignorance and lack of knowledge of the community about drilling and processing standards it can also result in environmental damage that can be widespread and can interfere with public health. In connection with the conditions mentioned above, this community service activity aims to provide education and technical guidance to illegal well miners through village head institutions (kepala dusun) and community leaders. It is hoped that this activity can provide standard examples (SOP) as a warning so that people avoid work accidents and casualties and protect the environment so that damage does not occur.